Análise das propriedades mecânicas do concreto convencional obtido a partir da adição de fibra artificial - Fonseca, Ayrton Táliton de Farias (Universidade Federal Rural do Semi-Árido, 2019)
The use of new materials in conjunction with concrete has been gaining more and more notoriety within the construction industry, with the purpose of obtaining new technologies and new construction methods. Such technologies are important in improving the characteristics in which conventional concrete does not perform well, such as the ability to withstand tensile stresses in flexion, which property tends to be improved with addition of fibers. The fibers appear as an addition option to conventional concrete, used mainly in industrial floors, lining of tunnels and etc. Polypropylene fiber is one of the types of materials that can be added to concrete to improve its properties. According to the literature, the main property that is improved with this addition is the tenacity of the concrete, making the compound have greater capacity to resist tensions soon after its first cracking, avoiding the appearance of new cracks, resulting in a higher resistance to flexion traction. The present work tries to analyze the mechanical properties of the conventional concrete obtained with addition of polypropylene fibers. For this, concrete dosages with 0.0-3.0, 4.5 and 6.0 kg / m3 of polypropylene fiber were carried out in a conventional concrete matrix, in addition, cone (slump test), axial compression strength and flexural tensile strength were performed. The experimental results showed that the most suitable content for addition of polypropylene fibers for the best influence of the concrete is 3.0 kg / m³, and the property that was most positively influenced was the tensile strength in flexion, with gain of 16.69% when compared to the reference concrete.
Monografia
Keywords: Concreto; Resistência à compressão; Resistência à tração; Fibra de polipropileno; Concrete; Compressive strength; Tensile strength; Polypropylene fiber; ENGENHARIAS::ENGENHARIA CIVIL